Analysis of Violation of Indonesian Advertisements in Starmaker Ads "Express Your Voice" which Deviates from Culture in Indonesia - Putra Hartadi, Nabeel; Ardianto, Reyhan; Krisnawati, Winda (Educationist: Journal of Educational and Cultural Studies, 2023)
Advertising is a strategy taken by companies to promote and inform the products it sells to the public. According to EPI (Indonesian Pariwara Ethics), advertising ethics are normative provisions concerning the advertising profession and business that have been agreed to be respected, adhered to, and enforced by all associations and development institutions. StarMaker is an app that allows users to sing karaoke songs for free and make friends with music. As for this article the method used by the author is a qualitative method using content analysis. In this study, the data collection method used is documentation, observation, and also content analysis of the Starmaker Application advertisement. It can be concluded that in this Starmaker application, there are still scenes that violate the Indonesian Advertising Ethics